Delayed Azithromycin Treatment Improves Recovery After Mouse Spinal Cord Injury - Kopper, Timothy J.; McFarlane, Katelyn E.; Bailey, William M.; Orr, Michael B.; Zhang, Bei; Gensel, John C. (Frontiers in Cellular Neuroscience, 2019)
After spinal cord injury (SCI), macrophages infiltrate into the lesion and can adopt a wide spectrum of activation states. However, the pro-inflammatory, pathological macrophage activation state predominates and contributes to progressive neurodegeneration. Azithromycin (AZM), an FDA approved macrolide antibiotic, has been demonstrated to have immunomodulatory properties in a variety of inflammatory conditions. Indeed, we previously observed that post-SCI AZM treatment reduces pro-inflammatory macrophage activation. Further, a combined pre- and post-injury treatment paradigm improved functional recovery from SCI. Therefore, for the current study, we hypothesize that post-injury AZM treatment will improve recovery from SCI. To test this hypothesis, we examined the therapeutic potential of delayed AZM treatment on locomotor, sensory, and anatomical recovery. We administered AZM beginning 30-minutes, 3-hours, or 24-hours following contusion SCI in female mice, and then daily for 7 days. AZM administration beginning 30-minutes and 3-hrs post-injury improved locomotor recovery with increased stepping function relative to vehicle controls. Further, delaying treatment for 30-minutes after SCI significantly reduced lesion pathology. Initiating AZM treatment 24-hour post-injury was not therapeutically effective. Regardless of the timing of the initial treatment, AZM did not statistically reduce the development of neuropathic pain (mechanical allodynia) nor increase neuron survival. Collectively, these results add to a growing body of evidence supporting AZM’s translational potential as a therapeutic agent for SCI and other neuroinflammatory conditions in which patients currently have very few options.